2016
DOI: 10.1111/tmi.12659
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HTLV‐1 and HTLV‐2 amongst mothers and children in Malawi within the context of a systematic review and meta‐analysis of HTLV seroprevalence in Africa

Abstract: ObjectivesHuman T‐lymphotropic virus (HTLV)‐1 causes T‐cell leukaemia and myelopathy. Together with HTLV‐2, it is endemic in some African nations. Seroprevalence data from Malawi are scarce, with no reports on associated disease incidence. HTLV seroprevalence and type were tested in 418 healthy mothers from Malawi. In addition, we tested the sera of 534 children to investigate mother‐to‐child transmission. To provide context, we conducted a systematic review and meta‐analysis of HTLV seroprevalence in African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…However, the situation of HTLV-1 in Africa is not well known. Indeed, the majority of previous studies have been carried out either on very specific populations such as pregnant women, blood donors or hospitalized patient series, or in heterogeneous and relatively small groups of rural or urban inhabitants of a specific town or village or area [ 5 , 13 ]. All these groups are far from being representative of the population of a given region or country.…”
Section: Introductionmentioning
confidence: 99%
“…However, the situation of HTLV-1 in Africa is not well known. Indeed, the majority of previous studies have been carried out either on very specific populations such as pregnant women, blood donors or hospitalized patient series, or in heterogeneous and relatively small groups of rural or urban inhabitants of a specific town or village or area [ 5 , 13 ]. All these groups are far from being representative of the population of a given region or country.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the regional prevalences of HTLV in adults from Fox et al . and assuming an annual incidence of ATLL among adult (40+) carriers of HTLV‐1 in Africa of 40 per 10 5 in males and 25 per 10 5 in females, about 1,400 cases of ATLL (all in SSA) would be caused by HTLV‐1 in Africa in 2018.…”
Section: Resultsmentioning
confidence: 99%
“…[101][102][103][104] A systematic review of studies in 25 African countries found the average seroprevalence of HTLV-1 in NA to be 0%, 1.2% in Eastern and Southern Africa and 3.2% in Western and Central Africa. 17 ATLL occurs in older adults in Japan, and is very rare under the age of 40, but seems to be more common among younger individual elsewhere. In a review of the incidence of ATLL among carriers of HTLV-1 in Japan, Iwanaga et al 105 found the rate to be about 60 per 100,000, 1.35 times higher in males than females.…”
Section: Htlv-imentioning
confidence: 99%
See 1 more Smart Citation
“…48 Few prevalence data are available for HTLV1/2 in SSA; when available, estimates are frequently based on accessible populations (e.g., blood donors and pregnant women). 49 A review found that the HTLV1 prevalence in healthy volunteers ranged from 0% (Zambia) to 13.07% (Gabon) 50 ; more recently, a seroprevalence of 2.1% was reported among pregnant women in Gabon. 51 The epidemiology of transfusion-associated HTLV1/2 in SSA is uncertain.…”
Section: Hepatitis Virusesmentioning
confidence: 99%